Tinjauan Sistematis: Faktor-Faktor Gaya Atribusi Prestasi Akademik - Alto Kusumo Yondrian (Universitas Islam Tribakti Lirboyo Kediri, 2020)
Attribution style is one of the most relevant concepts in predicting academic achievement. Various researches have tried to study the factors that influence the attribution style. Several factors such as gender, ethnicity, and social class have been widely discussed in scientific publications. However, since Bernard Weiner first developed attribution theory more than 40 years ago, there have been changes in a social condition that might have affected various attribution factors. This review aims to see the latest developments in the factors that influence the attribution of academic achievement. A systematic search of articles published in 3 English-language international publishers since 2010 identified a total of 6 studies, which included 132.293 students from various nations. An assessment that measured qualities of a research in 4 areas: research design, sampling, measurement, and analysis identified 3 high-quality research and 3 moderate-quality research. The result shows that ethnic factors confirm the findings from previous studies. Researches on gender factors provide new insights regarding the attribution style of female students. Besides, new factors emerge, such as school stratification and the attribution style of parents over their life events.